PENGADAAN BAHAN OLAHAN MAKANAN DI PURCHASING SECTION GRAND JATRA HOTEL PEKANBARU PROPINSI RIAU - Sumiati, Nita; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Tourism is a composite of activities, services, and industries that deliver a travel experience: transportation, accommodations, eating and drinking establishments, shops, entertainment, activity facilities and other hospitality services available for individuals or groups that are traveling away from home. Hotel is a species of accommodations that use a building or part of its, available: accomodation service, food and beverage service and also another services for public and managed for commercial goal. Food and beverage sales has been one of revenue source. Food and beverage sales can not be separeted of product section or we called “Kitchen”. The material will handle by Purchasing Section. Purchasing will purchase to some Supplier.The purpose of this reseacrch is to give a product procurement overview by Grand Jatra Hotel Pekanbaru Purchasing Section to get quality food product and revenue optimizing of food sales. This reserach will be describe about materials of food product procurement (from request process until delivery process), Purchasing Section’s responsibility and matters. Focus on cycle of procurement, requesting process, pre-purchase activity, delivery process and quality of product. Use some theory by Andrew Hale Feinstein & John M. Stefanelli, John. R Walker, Bartono PH & Ruffino aboout cycle, responsibiility of Purchasing Section and quality of Perishable product. Design by qualitative method, interview, observation and documentations. Give some statement to request informant’s rating and held observation. The indicators that want to present and and analyze by interval size as the type of measurement, while the formula used is the Likert Scale i = .Purchasing Grand Jatra Hotel Pekanbaru responsibility when requesting process rated by “Netral” (3, 38). Pre-purchase activity (2, 46) with “Less Good” category. Responsibilty when delivery process (2, 01) with “Less Good” category. There are matters and constraits in every process. Grand Jatra Purchasing section should looking for some solution or new improvement to be better.Keywords: Procurement of Food Product, Purchasing Section, Requesting and Delivery Process, Grand Jatra Hotel Pekanbaru.